2016
DOI: 10.1002/2016jc012192
|View full text |Cite
|
Sign up to set email alerts
|

The diurnal cycle of sea-surface temperature and estimation of the heat budget of the Mediterranean Sea

Abstract: The diurnal cycle in sea‐surface temperature (SST) is reconstructed for the year 2013 by combining numerical model analyses and satellite measurements using Optimal Interpolation (OI). The method is applied to derive hourly Mediterranean SST fields using Spinning Enhanced Visible and Infrared Imager (SEVIRI) data and Mediterranean Forecasting System analyses (Copernicus Marine Environment Monitoring Service ‐ Analysis and Forecast product). The evaluation of the Diurnal OI SST (DOISST) values against drifter m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
41
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 76 publications
5
41
0
3
Order By: Relevance
“…Diurnal warming of the upper ocean is caused by the daytime absorption of solar radiation. It has a significant influence on both air‐sea heat and gas fluxes (e.g., Clayson & Bogdanoff, ; Kettle et al, ; Marullo et al, ; Ward, ; Weihs & Bourassa, ) and sea surface temperature (SST) at longer time scales (e.g., Bernie et al, , ; Guemas et al, ; Shinoda et al, ). While the typical magnitude of diurnal warming of SST (dSST) is O(0.1 °C; e.g., Kennedy et al, ; Stuart‐Menteth et al, ), it may reach 5–7 °C on days with low wind speed and strong insolation (e.g., Gentemann et al, ; Gentemann & Minnett, ).…”
Section: Introductionmentioning
confidence: 99%
“…Diurnal warming of the upper ocean is caused by the daytime absorption of solar radiation. It has a significant influence on both air‐sea heat and gas fluxes (e.g., Clayson & Bogdanoff, ; Kettle et al, ; Marullo et al, ; Ward, ; Weihs & Bourassa, ) and sea surface temperature (SST) at longer time scales (e.g., Bernie et al, , ; Guemas et al, ; Shinoda et al, ). While the typical magnitude of diurnal warming of SST (dSST) is O(0.1 °C; e.g., Kennedy et al, ; Stuart‐Menteth et al, ), it may reach 5–7 °C on days with low wind speed and strong insolation (e.g., Gentemann et al, ; Gentemann & Minnett, ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of incorporating sea surface temperature (SST) diurnal variations (DVs) into numerical weather prediction (NWP) or climate models is becoming more recognized (e.g., Masson et al, 2012;Stuart-Menteth et al, 2003;Takaya et al, 2010). Including SST DV effects has been demonstrated to more accurately represent the air-sea interaction and therefore is expected to enhance air-sea coupled, NWP, and climate model performance (e.g., Brunke et al, 2008;Clayson & Bogdanoff, 2013;Halpern & Reed, 1976;Li et al, 2001;Marullo et al, 2016). For instance, Clayson and Bogdanoff (2013) have shown that including SST DV effects results in up to 10 W m 22 yearly average heat flux difference over significant portions of the tropical oceans.…”
Section: Introductionmentioning
confidence: 99%
“…A diurnal warm layer typically has a temperature difference relative to the water body below on the order of 0-3 K; but in some cases, it can reach values up to 5-8 K (e.g., Gentemann et al, 2008;Karagali & Høyer, 2014). Past studies on SST DV ranged from the determination and characterization of DV events (e.g., Clayson & Weitlich, 2005;Eastwood et al, 2011;Gentemann et al, 2008;Karagali & Høyer, 2014;Kawai & Wada, 2007;Soloviev & Lukas, 1997;Sverdrup et al, 1942;Zhang, Beggs, Majewski, et al, 2016) to the roles of DV events in air-sea interaction (e.g., Clayson & Bogdanoff, 2013, Halpern & Reed, 1976Li et al, 2001;Marullo et al, 2016) and to their impacts on long-term climate patterns (e.g., Masson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%